Effect of Human Resources, Leadership Style, The Use of Information Technology and Internal Control on the Quality of Financial Statements - Trisdina Mardinan; Muhammad Dahlan; Furry Khristianty Fitriyah (Universitas Padjadjaran, 2018)
This study aims to examine Whether there is a significant influence of variable humanresources competency, leadership, utilization of information technology, internal control of thequality of financial statements either partially or simultaneously. The population in this researchis all work units (SATKER) within the Directorate General of Construction Materials for 15 unitsof work with 45 respondents consisting of a financial assistance of the work unit, the Accountingofficer of Accrual Based Institution (SAIBA) and State-Owned Officer (BMN). The primary usedthe data Obtained from respondents through questionnaires, for testing the data tested the validity,reliability test and hypothesis testing. The Data then in the analysis with the analysis method usedis multiple linear regression. The results Showed that the competence of human resources,leadership style, technology utilization, and internal control Affect the quality of financialstatements either partially or simultaneously